Illusionism in sacred monumental painting of the baroque era, optics of perception - Tkachuk, Ilona; Lysun, Yaryna; Hrynda, Bohdana; Shymin, Yaroslav; Yankovska, Daria (Linguistics and Culture Review, 2021)
The investigation of the mechanisms of dual influence in a pair “work of art – viewer” opens up important opportunities for the worldview, cultural, aesthetic intentions laid down by the author(s), outlines the ways of transmitting the message to the recipient and assesses the effectiveness. The authors of this article analyse the practices of applying the mechanisms and principles of neuroaesthetics in the perception of baroque monumental paintings and the effects caused by the conscious use of illusory techniques in the duality of relationships. The authors of the article aim to find out the principles of the formation of cognitive and aesthetic connections expressed in specific formal principles-approaches, in the processes of perception of illusionistic baroque painting by the primary addressee-a person of the Baroque era – from the point of view of neuroaesthetics. The methodology refers to the implementing a multidisciplinary approach, based on the synthesis of cultural, anthropological and art research methods. To solve research problems and achieve results, we turn to the functional method and the modelling method, thanks to which defining effective models of interaction in the pair “work of art – recipient” and modes of functioning of consciousness when generating a pictorial image.